Marcado y Certificación de Recipientes a Presión Conforme a la Sección VIII, Div. 1 del Código ASME - Rivera Mendoza, Orlando R. (My University, 2005)
STAMPING DIRECTLY ON THE VESSEL When code stamping is applied directly on the vessel, stamping must: -Done using letters and figures at least 5/16” high. -Be arranged per figure UG-118 where space permits.
Keywords: Recipientes a presión; Stamping directly on the vessel, stamping on a nameplate, mode of inspection, type of construction, special service, degree of radiography, postweld heat treatment, code nameplate UG-118, parts of vessels, removable parts, miniature vessels, UG-90 (c)(a) vessels, renewal of code symbol stamps, manufacturer´s data reports